Optimalisasi Perundingan Bipatrit Sebagai Master Mind Penyelesaian Sengketa Pemutusan Hubungan Kerja (PHK) Sebagai Akibat Dari Pandemi Corona - Muhammad Ridwan; Lukman Ilman Nurhakim (Departemen Hukum Perdata, 2020)
Corona pandemic, which began to spread throughout the world since the beginning of 2020, caused various social problems, one of which was legal problems. The losses incurred in addition to involving Health, also the economic recession that caused many companies to lay off thousands of employees caused problems in Industrial Relations Dispute Resolution. The Manpower Act as a protective fence for Workers is supported by UUPPHI as a formal law, in fact it is quite overwhelmed in accommodating the needs related to Layoff Dispute Resolution. However, the Bipatrit Negotiation mechanism should be able to provide answers to existing problems. Judging from the simplicity and speed in its implementation, it can become a Master Mind in resolving the layoffs that are rife. But all this can be realized with the support of the principle of good faith the parties who should be implemented both when the Bipatrit Negotiations take place, as well as when implementing the Joint Agreement. The role of Bipatrit Negotiations is very much needed in resolving PHK disputes as a result of the Corona Pandemic to realize an effective and efﬁ cient dispute resolution for the realization of legal certainty and usefulness. In addition, it is necessary to concretize the qualiﬁ cations of good faith, especially in this Bipatrit Negotiations in order to make the Bipatrit Negotiations a Master Mind for the resolution of PHK disputes as a result of the Corona Pandemic.